Свобода як головний елемент формування громадянського суспільства. - Алікова, Олена Михайливна; Аликова, Елена Михайловна; Alikova, Е. (My University, 2011)
Institute of freedom in aspect of certain type of society forming is exam- ined in article, in particular, the question is about forming of civil society. In the article the basic approaches and conceptions to understanding of this socio-political institute are presented and outgoing moments for an origin and forming in society of realization of freedom degree and responsibility are determined.
Алікова О.М.Свобода як головний елемент формування громадянського суспільства. / О.М.Алікова // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2011. - Вип. 43. - С. 33 - 40.
Keywords: Суспільство; Формування громадянського суспільства; Соціологія; Свобода як елемент суспільства; Общество; Формирование гражданского общества; Социология; Свобода как элемент общества; society; Formation of civil society; sociology; Freedom as a member of society